Chemical functionalization of SnAs monolayer: a first-principles study of SnAsX (X = Cl, Br, and I) monolayers. (15th December 2022) - Vi, Vo T T; Nguyen, Cuong Q; Hoi, Bui D; Phuc, Huynh V; Nguyen, Chuong V; Hieu, Nguyen N
Abstract: Chemical functionalization is one of the effective methods to tune the electronic properties of two-dimensional (2D) nanostructures. In this paper, we study the structural, electronic properties, and carrier mobilities of 2D SnAs monolayer functionalized by chlorine, bromine, and iodine, namely SnAsX (X = Cl, Br, and I), by means of density functional theory. The obtained results show that the 2D SnAsX are energetically, dynamically, and mechanically stable. While the 2D pristine SnAs monolayer exhibits metallic characteristics, SnAsX monolayers are direct semiconductors with direct band gaps. The influence of spin–orbit coupling on the electronic characteristics of SnAsX is significant, especially in the case of SnAsI monolayer. The direct–indirect gap transitions are found in all three SnAsX monolayers when the biaxial strain is applied. Meanwhile, the effects of external electric fields on the electronic characteristics of SnAsX are insignificant. Our calculated results indicate that SnAsX monolayers have very high electron mobility and their transport characteristics are directionally isotropic along the investigated transport directions.